2022
DOI: 10.3389/fneur.2021.800189
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Cytokines in Children With Tic Disorder

Abstract: Tic disorder (TD) is a common childhood-onset disease associated with abnormal development of brain networks involved in the motor and sensory processing. The underlying pathophysiological mechanisms in TD are still unclear. An involvement of immune mechanisms in its pathophysiology has been proposed. This study investigates the association between the changes of cytokines and the etiology and development of TD. Different expressions of cytokines in a larger number of samples in our study may provide new insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Interleukin-6 ( IL-6 ) has both proinflammatory and anti-inflammatory activities ( 28 , 29 ) and contributes to the transition from acute inflammation to chronic inflammation ( 30 ). IL-6 is a multidirectional cytokine that has important roles in both the immune system and the nervous system, affecting mood, sleep, and neuroimmune regulation, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 ( IL-6 ) has both proinflammatory and anti-inflammatory activities ( 28 , 29 ) and contributes to the transition from acute inflammation to chronic inflammation ( 30 ). IL-6 is a multidirectional cytokine that has important roles in both the immune system and the nervous system, affecting mood, sleep, and neuroimmune regulation, among others.…”
Section: Discussionmentioning
confidence: 99%
“…compared tic disorder patients with controls, determining that patients had higher levels of IL-6 while levels of IL-2, IL-4, IL10, TNF-α, and IFN-γ were lower than controls [17]. Leckman et al also compared tic disorder patients and healthy controls, showing that the patients had elevated IL-12 and TNF-α levels [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the relationship between tic disorders and cytokines to identify the cytokines that play key roles. A recent research by Tao et al compared tic disorder patients with controls, determining that patients had higher levels of IL-6 while levels of IL-2, IL-4, IL10, TNF-α, and IFN-γ were lower than controls [ 18 ]. Leckman et al also compared tic disorder patients and healthy controls, showing that the patients had elevated IL-12 and TNF-α levels [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parker-Athill showed that TNF-α levels were associated with tic symptom exacerbation [ 17 ]. A Chinese study on 1724 tic disorder patients also showed that TNF-α among other cytokines increased in levels as symptoms get more severe, although statistical significance was not reached [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation